2024
DOI: 10.4252/wjsc.v16.i5.467
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells’ “garbage bags” at work: Treating radial nerve injury with mesenchymal stem cell-derived exosomes

Mazhar Mushtaq,
Doaa Hussein Zineldeen,
Muhammad Abdul Mateen
et al.

Abstract: Unlike central nervous system injuries, peripheral nerve injuries (PNIs) are often characterized by more or less successful axonal regeneration. However, structural and functional recovery is a senile process involving multifaceted cellular and molecular processes. The contemporary treatment options are limited, with surgical intervention as the gold-standard method; however, each treatment option has its associated limitations, especially when the injury is severe with a large gap. Recent advancements in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The reprogrammed cells are considered surrogate embryonic stem cells and are fast-emerging for theragnostic applications and disease modeling. Another important application of genetic modulation of MSCs is loading specific cargo of the transgene expression product in their derivate exosomes[ 85 ]. It has been observed that the exosomes released from the genetically modulated cells are rich in the gene expression product.…”
Section: Pretreatment Approaches Of Mscsmentioning
confidence: 99%
“…The reprogrammed cells are considered surrogate embryonic stem cells and are fast-emerging for theragnostic applications and disease modeling. Another important application of genetic modulation of MSCs is loading specific cargo of the transgene expression product in their derivate exosomes[ 85 ]. It has been observed that the exosomes released from the genetically modulated cells are rich in the gene expression product.…”
Section: Pretreatment Approaches Of Mscsmentioning
confidence: 99%